Khả năng suy luận thống kê của học sinh trung học phổ thông: Phân tích bằng mô hình Rasch - Phạm, Thế Quân; Trần, Trung (Tạp chí Giáo dục, 2024)
Among many models of the Item Response Theory (IRT), the Rasch model is the simplest and most commonly used. Mathematician George Rasch has built a simple question characteristic function model that is widely used today. In this paper, we apply the Rasch model of the Item Response Theory (IRT) to analyze test questions and statistical reasoning ability of high school students. The results of the experimental study were analyzed with quantitative methods, the data were processed with QUEST and SPSS 20.0 software. The research subjects were 108 grade 10 students of Binh Giang High School, Binh Giang District, Hai Duong Province. The research results showed that the test questions had high reliability, the distribution of difficulty of the questions in the test covered the students’ abilities. In terms of statistical reasoning, the surveyed students performed relatively well in basic skills such as calculating, reading and understanding charts presenting data. However, there were still limitations in applying statistical knowledge to analyze, explain and draw meaningful conclusions from given data. Another notable point is that there was no significant difference in statistical reasoning ability between male and female students.